Isolation and identification of cellulose-producing strain Komagataeibacter intermedius from fermented fruit juice. (20th October 2016) - Lin, Shin-Ping; Huang, Yin-Hsuan; Hsu, Kai-Di; Lai, Ying-Jang; Chen, Yu-Kuo; Cheng, Kuan-Chen
Highlights: The identified strain FST213-1 is a new isolate of Komagataeibacter group. Komagataeibacter intermedius FST213-1 is a base-resistant strain. FST213-1 produces 1.1 g/L of BC in 4 days at pH 9. Materials properties of BC from FST213-1 are revealed. Abstract: A bacterial cellulose (BC) producing strain isolated from fermented fruit juice was identified as Komagataeibacter intermedius (K. intermedius) FST213-1 by 16s rDNA sequencing analysis and biochemical characteristics test. K. intermedius FST213-1 can produce BC within pH 4–9 and exhibit maximum BC production (1.2 g/L) at pH 8 in short-term (4-day) cultivation. Results of Fourier transform infrared spectroscopy, X-ray diffraction, water content, thermogravimetric analysis and mechanical property indicated that BC produced from K. intermedius FST213-1 exhibits higher water content ability (99.5%), lower thermostability (315 °C), lower crystallinity (79.3%) and similar mechanical properties in comparison with the specimen from model BC producer, Gluconacetobacter xylinus 23769. Based on these analyses, the novel based-resistant strain K. intermedius FST213-1 can efficiently produce BC, which can be applied for industrial manufacturing with potential features.